Conservation and ecological screening of small water bodies in temperate riverine wetlands using UAV Photogrammetry (Middle Danube) - Dušanka Cvijanović; Maja Novković; Djuradj Milošević; Milica Stojković Piperac; Laszlo Galambos; Dubravka Čerba; Olivera Stamenković; Bojan Damnjanović; Minučer Mesaroš; Dragoslav Pavić; Vladica Simić; Ivana Trbojević; et al. (Nature Conservation)
Aquatic ecosystems in riverine wetlands are important refuges and nurseries for freshwater biota. Given the significant global loss and degradation of wetlands, regular conservation assessments of these habitats, even in not easily accessible regions, are crucial for implementing effective management. Thus, developing cost-effective approaches for rapid ecological and conservation screening of water bodies in floodplains, such as the Danube, is a priority. One potential solution is the use of UAV-based (Unmanned Aerial Vehicle) ecological indicators to complement existing monitoring frameworks. This paper aims to explore whether UAV-based macrophyte data can provide a more precise indication of the trophic state and conservation indices (assessed through fish and macroinvertebrate communities) of temperate wetland lentic ecosystems, compared to traditional field surveys. The fieldwork was conducted during the summer months of 2019 at 23 sampling sites within eight lentic water bodies located in three wetland areas along the Middle Danube in Serbia. Data on aquatic vegetation, fish, and macroinvertebrate communities, and samples for water quality analysis were collected simultaneously. UAV images were acquired using an RGB camera. Orthomosaics were processed using supervised object-based image (OBIA) classification to obtain a single vector layer with macrophyte functional groups and taxa. Macrophyte cover metrics obtained during the fieldwork and UAV data processing were correlated against water quality parameters and conservation indices calculated for fish and macroinvertebrate assemblages. The study demonstrated that UAV photogrammetry can provide relatively precise measurements of macrophyte cover characteristics compared to traditional plot-based monitoring methods, making it effective for assessing aquatic ecosystems. The analysis revealed that sites with high values of fish and macroinvertebrate conservation indices, optimal oxygen conditions, and mesotrophic states were associated with UAV orthomosaic polygons showing relatively high macrophyte functional diversity and a presence of floating-rooted species. Conversely, sites experiencing eutrophication and a poor oxygen regime with species-poor fish assemblages correlated positively with a higher cover of amphibian and free-floating vegetation, as well as filamentous algae. In conclusion, UAV photogrammetry offers a cost-effective method to monitor aquatic habitats along large river floodplains, including those that are not easily accessible.